Tribe : why do all our friends look just like us? - Unger, Sandra Mayes (Fortress Press, 2020)
"Tribe explores the issues of reciprocity in cross-race and cross-class relationships using stories, narrative, and sociological insights and perspectives derived from urban fieldwork and the author's own life. The volume examines the social and structural barriers to the formation of these kinds of relationships, as well as the transformations that can take place as these barriers are overcome. Stories, interviews, and empirically driven narratives are interwoven with theory from the fields of adult education, economics, sociology, ethics, theology, and history. After exploring the barriers to the formation of these relationships and the potential of adults for learning new ways of thinking and being, the book makes the case that there are communal and individual benefits to these relationships that far outweigh the difficulties in forming them. The book is set up to answer the questions "Why does it matter if all my friends look just like me?" and "How do I leave behind a siloed existence to live a fully transformational and socially aware life?""--